Factors facilitating trained NIMART nurses' adherence to treatment guidelines: a vital matter in the management of TB/HIV treatment in South Africa - Lufuno Makhado; Mashudu Davhana-Maselesele; Rachel Tsakani Lebese; Sonto Maria Maputle (BMC, 2020)
Abstract Background Globally, the burden of tuberculosis or human immunodeficiency virus (TB/HIV) is at 24% and this alarming rate compelled the World Health Organization (WHO) to declare the African region as a critical workforce shortage area. To facilitate adherence to treatment guidelines, WHO recommended a strategy of task shifting for countries with high health workforce shortages. The strategy aimed at the redistribution of health care tasks to available workers. The study aimed to determine the factors facilitating nurse-initiated management of antiretroviral therapy (NIMART) trained nurses' adherence to TB/HIV treatment guidelines. Methods The study employed an exploratory-descriptive design. The study was conducted in Ugu and Ngaka Modiri Molema Districts of KwaZulu-Natal (KZN) and North West (NW) Provinces of South Africa. The population comprised of 24 participants who were purposively selected. The in-depth focus group discussions were conducted and ATLAS T.I. was used for data analysis following the basic steps of notice-collect-think (NCT) analysis. Trustworthiness and adherence to ethics were ensured. Results The singular theme of factors facilitating NIMART trained nurses' adherence to treatment guidelines which included positive attitudinal needs and positive behavioural change emerged from raw data. Conclusion Continuous training, support supervision, and improved relationships with colleagues need to be enhanced to enable NIMART trained nurses to adhere to treatment guidelines.